1994
DOI: 10.1159/000462587
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Post-Transfusion Hepatitis before and after Screening for Hepatitis C Virus Antibody

Abstract: To evaluate the effectiveness of screening test for antibody to hepatitis C virus (anti-HCV), the incidence of acute post-transfusion HCV infection in patients who underwent cardiovascular surgery and received blood transfusion was studied. All patients were followed prospectively with serum biochemistry tests and viral hepatitis markers before and periodically for at least 6 months after cardiovascular surgery. None of them had history of liver disease and none tested positive for anti-HCV prior to blood tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…As HCV infection is traditionally transmitted via the blood, post-transfusion hepatitis due to HCV infection accounts for the high rates of hepatitis in this setting [Alter et al, 1989;Esteban et al, 1990;Aach et al, 1991;Lee et al, 1991b;Watanabe et al, 1994]. However, since the implementation of specific testing for anti-HCV in donated blood, transmission by blood products was effectively reduced [Donahue et al, 1992;Wang et al, 1994Wang et al, , 1995. Our case-control study showed that a history of blood transfusion was related significantly to anti-HCV seropositivity, as has been documented in previous studies of blood transfusion recipients [Alter et al, 1989;Esteban et al, 1990;Aach et al, 1991].…”
Section: Discussionmentioning
confidence: 99%
“…As HCV infection is traditionally transmitted via the blood, post-transfusion hepatitis due to HCV infection accounts for the high rates of hepatitis in this setting [Alter et al, 1989;Esteban et al, 1990;Aach et al, 1991;Lee et al, 1991b;Watanabe et al, 1994]. However, since the implementation of specific testing for anti-HCV in donated blood, transmission by blood products was effectively reduced [Donahue et al, 1992;Wang et al, 1994Wang et al, , 1995. Our case-control study showed that a history of blood transfusion was related significantly to anti-HCV seropositivity, as has been documented in previous studies of blood transfusion recipients [Alter et al, 1989;Esteban et al, 1990;Aach et al, 1991].…”
Section: Discussionmentioning
confidence: 99%
“…Quando comparamos os grupos com os resultados de HCV-RNA, observamos que o único paciente do grupo após 1993 é negativo. Nossos dados também são semelhantes aos encontrados por Makris et al 28 e Wang et al 34 , que demonstraram maior presença de infecção pelo HCV em hemofílicos que iniciaram tratamento em data anterior à triagem sorológica obrigatória para HCV, quando comparados com os que iniciaram tratamento após. Na nossa amostra não houve pacientes com viremia para HCV (HCV-RNA positivo) após o início da triagem obrigatória de doadores.…”
Section: Discussionunclassified
“…A sharp drop in post-transfusional hepatitis C was obser ved since the state-of-the-art screening assays of HCV antibodies were applied to blood donors [4,5] . However, patients of post-transfusion and sporadic hepatitis C infection were still reported for the presence of preseroconversion window period (PWP), in which antibody detection was not able to identify subjects in the early stage of infection.…”
Section: Introductionmentioning
confidence: 99%